Invisible women : data bias in a world designed for men [book club bag] - Criado-Perez, Caroline (Abrams Press, 2021)
Data is fundamental to the modern world. From economic development to health care to education and public policy, we rely on numbers to allocate resources and make crucial decisions. But because so much data fails to take into account gender, because it treats men as the default and women as atypical, bias and discrimination are baked into our systems. And women pay tremendous costs for this bias, in time, money, and often with their lives. The author investigates this shocking root cause of gender inequality. Examining the home, the workplace, the public square, the doctor's office, and more, the author uncovers a dangerous pattern in data and its consequences on women's lives. Product designers use a 'one-size-fits-all' approach to everything from pianos to cell phones to voice recognition software, when in fact this approach is designed to fit men. Cities prioritize men's needs when designing public transportation, roads, and even snow removal, neglecting to consider women's safety or unique responsibilities and travel patterns. And in medical research, women have largely been excluded from studies and textbooks, leaving them chronically misunderstood, mistreated, and misdiagnosed. Built on hundreds of studies in the US, the UK, and around the world, this is an exposé that will change the readers look at data and the world. --